A history of American literature - Gray, Richard J. (Wiley-Blackwell, 2011)
"Updated throughout and with much new material, A History of American Literature, Second Edition, is the most up-to-date and comprehensive survey available of the myriad forms of American Literature from pre-Columbian times to the present? The most comprehensive and up-to-date history of American literature available today? Covers fiction, poetry, drama, and non-fiction, as well as other forms of literature including folktale, spirituals, the detective story, the thriller, and science fiction? Explores the plural character of American literature, including the contributions made by African American, Native American, Hispanic and Asian American writers? Considers how our understanding of American literature has changed over the past?thirty years Situates American literature in the contexts of American history, politics and society Offers an invaluable introduction to American literature for students at all levels, academic and general readers"--